CCAR1/CoCoA pair‐mediated recruitment of the Mediator defines a novel pathway for GATA1 function. (19th November 2013) - Mizuta, Shumpei; Minami, Tomoya; Fujita, Haruka; Kaminaga, Chihiro; Matsui, Keiji; Ishino, Ruri; Fujita, Azusa; Oda, Kasumi; Kawai, Asami; Hasegawa, Natsumi; Urahama, Norinaga; Roeder, Robert G.; et al.
<x xml:space="preserve">Abstract</x> The MED1 subunit of the Mediator transcriptional coregulator complex coactivates GATA1 and induces erythropoiesis. Here, we show the dual mechanism of GATA1‐ and MED1‐mediated transcription. MED1 expression levels in K562 erythroleukemia cells paralleled the levels of GATA1‐targeted gene transcription and erythroid differentiation. An N‐terminal fragment of MED1, MED1(1–602), which is incapable of interacting with GATA1, enhanced GATA1‐targeted gene transcription and erythroid differentiation, and introduction of MED1(1–602) into Med1−/− mouse embryonic fibroblasts (MEFs) partially rescued GATA1‐mediated transcription. The C‐terminal zinc‐finger domain of GATA1 interacts with the MED1(1–602)‐interacting coactivator CCAR1, CoCoA and MED1(681–715). CCAR1 and CoCoA synergistically enhanced GATA1‐mediated transcription from the γ‐globin promoter in MEFs. Recombinant GATA1, CCAR1, CoCoA and MED1(1–602) formed a complex in vitro, and GATA1, CCAR1, CoCoA and MED1 were recruited to the γ‐globin promoter in K562 cells during erythroid differentiation. Therefore, in addition to the direct interaction between GATA1 and MED1, CoCoA and CCAR1 appear to relay the GATA1 signal to MED1, and multiple modes of the GATA1‐MED1 axis may help to fine‐tune GATA1 function during GATA1‐mediated homeostasis events.